Polymer electrolytes for electrochromic devices through solvent casting and sol-gel routes - Leones, Rita Daniela Barros (2017)
Ionically conductive membranes of gelatin and d-PCL(530)/siloxane doped with cyano-based ionic liquids (ILs) were prepared through solvent casting and sol-gel methods, respectively. The membranes were characterized in terms of ionic conductivity, thermal behavior, morphology, and structure. All samples, except the d-PCL(530)/siloxane matrix, exhibited a predominantly amorphous morphology. The samples prepared through solvent casting and sol-gel displayed a minimum thermal stability of 170 and 230 ºC, respectively. The ionic conductivity varied accordingly with the type, quantity, and length of the alkyl chain of the cation of the ILs. The sample with the highest ionic conductivity was gelatin0.5[C2mim][N(CN)2] with 2.40 x 10-3 S. cm-1 at 25 ºC and 1.68 x 10-2 S. cm-1 at 95 ºC. The good results of ionic conductivity encouraged the assembly and characterization of prototypes of electrochromic devices (ECDs). The best results were obtained with glass/ITO/WO3/gelatin1[C2mim][SCN]/CeO2-TiO2/ITO/glass configuration that showed a fast color switching time (~ 15 s) and a good open circuit memory (~ 4 hours). The ECD changed its color from pale blue to transparent, and its charge density decreased from -17.53 to - 2.71 mC. cm-2 during 640 color/bleaching cycles.